Oppositions and their Member Nominations in the Conflict Communication Discourse of Rolandas Paksas (2003–2004) - Linkevičiūtė, Vilma (Respectus Philologicus, 2013)
The object of this article is the linguistic means of political conflict communication that are characteristic of the political discourse of the former President of the Republic of Lithuania, Rolandas Paksas (2003–2004). In modern democratic societies, political life is founded upon the actions of political parties, their duly elected leaders, and various political ideologies. In this context, political discourse, which records a variety of opinions and, frequently, their conflict, becomes an inseparable element of political culture. Conflict communication in political discourse may be perceived as the main research object of political linguistics, because the attack and winning of governmental positions occur in the context of the conflict of various political forces. That conflict is expressed through discourse. The aim of this study is to analyze how conflict communication was manifested in Lithuania during the period from 2003 to 2004. In political communication, an initial situation of verbal and non-verbal actions can become a source of conflict, while disapproval of such a situation is verbalized in political communication. Any individual who wants to influence political events becomes the subject of such communication. Moreover, this article discloses the fact that linguistic means are closely related to the ideology of the speaker and linguistic practices are conditioned by culture.
Keywords: Conflict Communication; Political Discourse; Domain; Meaning Field; Concept